MHD Flow of a Casson Fluid Over An Exponentially Shrinking Sheet - Rasol, Nurul Aini Nabilah; Md Shah, Noorzehan Fazahiyah (Enhanced Knowledge in Sciences and Technology, 2024)
In this study, the MHD flow of a Casson fluid over an exponentially shrinking sheet is studied. The governing partial differential equations were transformed to a system of nonlinear ordinary differential equations using a similarity transformation. Next, the governing equation was solved using bvp4c technique in Matlab to obtain the results with various parameters such as Casson fluid parameter, γ, shrinking parameter, s and Hartmann number, M. The profiles act as a result are analysed and discussed. It is found that an increase in the Casson fluid parameter γ reduces the velocity profile because the flow stress decreases as γ increases. With increasing magnetic interaction parameter M and suction parameter s, the magnitudes of velocity decrease significantly.